EVALUASI PENGGUNAAN BAHAN KIMIA BERBAHAYA PADA PRODUK PERIKANAN DI KOTA MAKASSAR - Nursinah Amir; Chanif Mahdi (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2018)
This research aims to determine the use of hazardous chemicals in fishery products that are marketed in the city of Makassar. In this study used the Accidental Sampling Technique. Samples are taken from the center of Makassar souvenirs, traditional markets, and modern markets. The fishery products used as samples are crackers, meatballs, and brains. Hazardous chemicals evaluated for use are borax and formalin. The samples were analyzed using a test kit and colorimeter at the BIOCHEME Laboratory (Healthy Food) Department of Chemistry,University of Brawijaya. The results show that fish meatball products marketed in Makassar City do not contain borax, but contain formalin 11.2 - 13.13 ppm. Brain-brain products do not contain borax and do not contain formaldehyde, fish/shrimp crackers marketed in Makassar City do not contain formaldehyde but 33% contain borax with an average, level of 10.39 ppm.